Fiscal Policy Directions Of Small Enterprises and Anti-Crisis Measures on Modern Stage: During the Transformation of Georgia to the EU - George Abuselidze (Science and Studies of Accounting and Finance: Problems and Perspectives, 2018)
The paper is aimed to determine the optimality of taxation, that can be used to plan and implement effective anti-crisis measures. Objective is not to define or diagnose crisis and suggest strategies, but to offer methodologies, that can be used to determine the influence of formal and informal institutions of company's ongoing activities. To develop recommendations for avoiding business crisis situation and support its development. The theoretical and methodological basis of the research is the main provisions of the market economy, legislative and regulatory acts of Georgia and foreign countries, statistical data of Georgia, the global risks report, government bodies and business structures in this field. In the process of analysis of the actual material, together with the general scientific method of research, is used: systemic analysis, comparative analysis of scientific literature, statistical analysis, analogy and other methods. As a result of researches it is established that developed countries emphasize the importance of fairness, while developing countries are mainly focused on mobilizing budget revenues and lesser consideration of fair taxation principles, since the tax system performs a fiscal function more effectively than developing countries. In our opinion, the main idea of tax policy should be the optimal distribution of tax literacy on the basis of a direct definition of income of taxpayers or progressive taxation. Practical implementation of the proposed proposals will facilitate further improvement of the social climate in the country, revitalize small and medium businesses, and solve the problem of employment in the country.
Keywords: E62; G30; H30; 330; Fiscal Policy; Financial Crises; Crisis Management; Small Business; Social Stimulation